A Deep Eutectic Solvent based novel drilling mud with modified rheology for hydrates inhibition in deep water drilling - Rasool, M.H. (Elsevier B.V., 2022)
Ionic liquids are well-liked drilling fluid additives for inhibiting hydrates and modifying mud rheology. However, preparation of ionic liquid is costly and imidazolium based ionic liquids have been found to be severely toxic. Deep Eutectic Solvent (DES) is a non-toxic and cheaper alternative of traditional ionic liquids. In this research, in-house prepared, Choline chloride and Urea based DES has been used as a drilling fluid additive in water based mud. Micro-DSC has been used to study the induction time of methane gas hydrates at 114 bar between â20 Â°C to 20 Â°C. Drilling fluid rheology and properties have been determined by following AP1 13B-1 standards. The results of Micro DSC evidenced that the addition of DES delayed the induction time of the hydrates up to 24.3, improved the YP/PV of the drilling fluid and also resulted into 20 and 14.5 reduction in filtrate volume and mud cake thickness respectively. Moreover, based upon the outcomes of characterizations i.e. Zeta potential, XRD and FTIR, it is proposed that the improvement in mud rheology is due to the change in clay's size and structure on interaction with DES. Consequently, the DES inhibits the hydrate formation and alters the mud rheology by its excellent ability to form hydrogen bonds with hydrates' crystals and clay granules respectively. Â© 2022 Elsevier B.V.